A New Approach to Innovation at Nestlé R&D. (January 2014) - Bauer, Werner
<x xml:space="preserve">Abstract</x> This article examines a successfully implemented innovation process at Nestlé's R&D headquarters in Switzerland. The six‐year experience uses a micro‐MBA model to train Nestlé employees in how to move beyond the traditional models and innovate far beyond technology, turning them into agents of change. Using nontraditional methods, the results achieved by the program have succeeded beyond expectations. In fact, this innovation process has turned the training into a profit opportunity for the company. © 2013 Wiley Periodicals, Inc.